ZnSe:Mn aqueous colloidal quantum dots for optical and biomedical applications. Issue 7 (13th May 2016) - Silva, Thiago G.; Moura, Igor M. R.; Filho, Paulo E. Cabral; Pereira, Maria I. A.; Filho, Clayton A. Azevedo; Pereira, Goreti; Pereira, Giovannia A. L.; Fontes, Adriana; Santos, Beate S.
Abstract: In this study, we present the optimization of the optical properties of Mn 2+ doped ZnSe QDs (also referred to as d‐dots) coated with thioglycolic acid in aqueous medium. The nanoparticles were characterized by ionic coupled plasma, electron paramagnetic resonance, transmission electron microscopy and X‐ray diffractometry. By applying a controlled dose of UV irradiation, we obtained efficient orange emitting d‐dots ( 4 T1 → 6 A1 transition centered at 580 nm). The results point out to a doping fraction in the nanoparticles smaller than 1% (0.89%), and that the Mn 2+ ions are preferentially located close to the particle's surface. The UV photoactivation procedure has a definite influence on the emission intensity and on the colloidal stability of the particles. Photoactivated Mn 2+ d‐dots were conjugated to Concanavalin A and labeled specifically Candida albicans yeast cells, by targeting carbohydrate residues depicting the successful use of these QDs as fluorescent probes. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)